Study on Hexavalent Chromium Reduction by Chromium Resistant Bacterial Isolates of Sukinda Mining Area - Mishra, V.; Samantaray, D.P.; Dash, S.K.; Mishra, B.B.; Swain, R.K. (Our Nature, 2011)
Rapid industrialization coupled with explosive development of chemical and mining industries has not only resulted in global deterioration of the environmental quality but also has drawn attention of scientists for an effective measure to control environmental pollution. Sukinda in the district of Jajpur, Orissa has drawn worldwide attention as one of the most polluted area with chromium due to chromate rich. In the present experiment, attempt has made to detoxify Cr (VI) by chromium resistant bacterial isolates of Sukinda mining area. Random soil and water samples were collected aseptically from four different sites of the mining area and physiochemical parameters of the samples were estimated. Out of the twelve, four chromium resistant bacterial isolates viz., Micrococcus luteus, Pseudomonas putida, Serratia marcescens and Acinetobacter calcoaceticus tolerated hexavalent chromium beyond 500 ppm and selected for reduction. Among all, Acinetobacter calcoaceticus shown highest amount of hexavalent chromium reduction of 67.14% incubated at 30°C for 24 hr at pH 7. Then Acinetobacter calcoaceticus was selected for parametric studies and observed to exhibit highest reduction i.e., 70.53% potential at pH 8.0, temperature 30°C/24 hr. Therefore, Acinetobacter calcoaceticus may be use in the bioremediation of hexavalent chromium toxicity. DOI: 10.3126/on.v8i1.4313